On the Coupler curve Equation or planar Inverse Four-bar Parallelogram Linkages - 谢进; 陈永 (Jixie chuandong)
The coupler curve equation of planar inverse four-bar parallelogram linkdges has been studied in this paper. The fourth order explicit analytical expression of the coupler curve has been derived using symbolic numerical technique.